2013
DOI: 10.1152/ajpheart.00604.2012
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin proteasome system and myocardial ischemia

Abstract: The ubiquitin proteasome system (UPS) has been the subject of intensive research over the past 20 years to define its role in normal physiology and in pathophysiology. Many of these studies have focused in on the cardiovascular system and have determined that the UPS becomes dysfunctional in several pathologies such as familial and idiopathic cardiomyopathies, atherosclerosis, and myocardial ischemia. This review presents a synopsis of the literature as it relates to the role of the UPS in myocardial ischemia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 173 publications
0
44
0
2
Order By: Relevance
“…Neither the irreversible/␤ 5 -specific (epoxomicin) nor the reversible/nonspecific (MG132) proteasomal inhibitors altered the degree of RVH or hastened the development of RVF, suggesting that the failing RV is not responsive to further proteasomal inhibition in this model of RV failure. Nevertheless, future studies are needed to study the effect of inhibitors being developed against the induced isoforms of proteasomes (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither the irreversible/␤ 5 -specific (epoxomicin) nor the reversible/nonspecific (MG132) proteasomal inhibitors altered the degree of RVH or hastened the development of RVF, suggesting that the failing RV is not responsive to further proteasomal inhibition in this model of RV failure. Nevertheless, future studies are needed to study the effect of inhibitors being developed against the induced isoforms of proteasomes (10).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in proteasomal function have been described well in models of left ventricular (LV) hypertrophy (LVH), ischemia-reperfusion (2,10,16), and dilated and desminrelated cardiomyopathies (13,49), as well as in human heart failure (47,49,72). However, studies have been contradictory, showing either increased or decreased proteasomal enzyme activity in the afterload stressed LV (31,43).…”
mentioning
confidence: 99%
“…28 We, therefore, tested our models for alterations in total protein ubiquitination. In the Langendorff-perfused mouse hearts, the amount of ubiquitinated proteins seemed unchanged between controls and I/R.…”
Section: Titin Ubiquitinationmentioning
confidence: 99%
“…Three proteasome subunits (PSMB1, -A2, -A6) were among the CSF proteins with increased post-HI levels. Several studies have demonstrated reversible proteasome dysfunction secondary to oxidative damage after HI [18]. Dysregulation with decreased activity may lead to accumulation of damaged proteins, and promote neurodegenerative or neurodevelopmental disorders [19].…”
Section: Proteins Altered In Csfmentioning
confidence: 99%